Serum Homocysteine and its Association with Lipid Profile in Type 2 Diabetic Patients (Journal of Shaheed Suhrawardy Medical College, 2018)
Background: Diabetes accounts for almost 6% of total global mortality, with 50% of diabetesassociated deaths being attributed to cardiovascular disease (CVD). Prevalence of type 2 diabetes in rural Bangladeshi and in urban Bangladeshi is found to be 7.2% and 10.5% respectively. People of developing countries suffer from the disease at earlier age than that of developed countries. Among the diabetic patients, vascular complications represent a major cause of morbidity and mortality. Diabetes is commonly accompanied by other cardiovascular risk factors: dyslipidemia, hypertension, and increased prothrombotic factors. Total plasma homocysteine (tHcy) is an emerging CVD risk factor. Insulin resistance and hyperinsulinemia in diabetes mellitus along with increased homocysteine is thought to cause endothelial dysfunction. Endothelial dysfunction together with other factors such as dyslipidemia, microalbuminemia etc. causes cardiovascular disease.Objectives: Objective of the study was to evaluate serum total homocysteine level and to correlate it with fasting lipid profile in type 2 diabetic patients.Methodology: This cross sectional study was conducted during the period of July 2011- June 2013 on 95 patients of type 2 diabetes mellitus, attending the Endocrine OPD of Bangabandhu Sheikh Mujib Medical University (BSMMU). The study was carried out in the Department of Biochemistry, Bangabandhu Sheikh Mujib Medical University, Shahbag, Dhaka. Study subjects were selected by purposive and convenient sampling technique.Result: Study subjects were categorized according to the presence or absence of hyperhomocysteinemia. Among the total study population hyperhomocysteinemia was found in 21.05 %. Among them number of male was greater. The study population had mean serum total cholesterol 198.34±39.62(mg/dl), triacylglycerol 198.91±116.71(mg/dl), LDL 126.75±35.38(mg/ dl), HDL 34.35±8.31(mg/dl), TC:HDL=15.67±6.07:1,and LDL:HDL=9.94±3.88:1 Independant sample t test showed that there was significant inverse association of hyperhomocysteinemia with HDL. Other parameters of lipid profile and lipid ratios did not show any significant association.Conclusions: Around one fifth of the type 2 diabetic patients had hyperhomocysteinemia. Significant inverse association was present between hyperhomocysteinemia and HDL. Other parameters of lipid profile and lipid ratios did not show any significant association.J Shaheed Suhrawardy Med Coll, June 2018, Vol.10(1); 42-46